ImageJ and CellProfiler: Complements in Open‐Source Bioimage Analysis. Issue 5 (26th May 2021) - Dobson, Ellen T.A.; Cimini, Beth; Klemm, Anna H.; Wählby, Carolina; Carpenter, Anne E.; Eliceiri, Kevin W
Abstract: ImageJ and CellProfiler have long been leading open‐source platforms in the field of bioimage analysis. ImageJ's traditional strength is in single‐image processing and investigation, while CellProfiler is designed for building large‐scale, modular analysis pipelines. Although many image analysis problems can be well solved with one or the other, using these two platforms together in a single workflow can be powerful. Here, we share two pipelines demonstrating mechanisms for productively and conveniently integrating ImageJ and CellProfiler for (1) studying cell morphology and migration via tracking, and (2) advanced stitching techniques for handling large, tiled image sets to improve segmentation. No single platform can provide all the key and most efficient functionality needed for all studies. While both programs can be and are often used separately, these pipelines demonstrate the benefits of using them together for image analysis workflows. ImageJ and CellProfiler are both committed to interoperability between their platforms, with ongoing development to improve how both are leveraged from the other. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Studying cell morphology and cell migration in time‐lapse datasets using TrackMate (Fiji) and CellProfiler Basic Protocol 2 : Creating whole plate montages to easily assess adaptability of segmentation parameters